Dangling between death and hope: An HIV and AIDS gender-sensitive re-reading of Psalm 6 - Masenya, Madipoane; Mtshiselwa, V. Ndikhokele N. (Verbum et Ecclesia, 2016)
The genre of laments (both individual and communal) can be traced historically, even up to today, to periods of crisis. The psalms of lament in the Hebrew Bible point to periods both of national crisis such as wars, exile, and individual crisis, namely attacks from enemies and illness among others. The crisis of the exile was typified by death (in the literal and metaphorical sense), pestilence, disease and war. It was also typified by hope as some of the prophets such as Jeremiah could prophesy both doom (read: death) and salvation (read: hope). If there is any crisis that people of African descent, particularly those located within the sub-Saharan continent, have ever come to experience it is the crisis brought by the pandemic of HIV and AIDS. The pandemic is better approached by scholars who hold the view that it is multisectoral. According to the latter view, the pandemic impacts the social, the economic, the religious or spiritual, and the psychological lives of both the affected and the infected. It is a justice issue. It can thus not be relegated to the individual because it is communal. Is it any wonder that in 2002 the members of the Circle of Concerned African Women Theologians set out to theologise and conduct God-talk that would be both gender- and HIV and AIDSconscious? In this article, we engage the works of Circle theologians and biblical scholars to see what kind of reading could emerge if we re-read the lament psalm, such as Psalm 6, gender and HIV and AIDS consciously. Intradisciplinary and/or interdisciplinary implications: In this article, the disciplines of biblical studies, gender studies, and HIV and AIDS studies, among others, converge as the authors draw from Circle theologies and biblical hermeneutics to re-read Psalm 6 through an HIV and AIDS lens. In the process, issues such as patriarchy, poverty and social justice are also dealt with. Keywords: Circle biblical hermeneutica; Psalm 6; HIV and AIDS; Gender-sensitive
free